Prevalence and Risk Factors of the Rheumatoid Arthritis in Herzegovina Region in 2003–2005 - Damjanović, Vesna (Array, 2009)
Summary: In this study we evidenced prevalence of the rheumatoid arthritis (RA) in Herzegovina region of the Bosnia and Herzegovina and studied selected RA risk factors. Sample of subjects comprised RA diagnosed subjects which were compared to randomly selected controls. In diagnosing the RA we used criteria for the classification of rheumatoid arthritis suggested by The American College of Rheumatology. Risk factors of RA included in this investigation were (1) educational status, (2) quality of nutrition, and (3) socioeconomic status. Average prevalence of the RA in our sample was 0.46/100, ranged from 0.36/100 to 0.64/100, which is comparable to other European samples. The RA occurrence is six times more often in females than in males. We have found indices that the Mediterranean diet has to be considered as protective factor against RA. Although RA occurrence is more frequent in the low socioeconomic samples of subjects, because of the methodological reasons we can not undoubtedly support the socioeconomic status as significant risk factor of the RA. Finally, it is interesting that we have found education level as risk factor significantly related to RA occurrence in our sample. All evidenced should be more precisely studied in some future study, while accurately controlling all relevant factors